Epidemiological Profile Of Patients With End Stage Renal Disease On Maintenance Hemodialysis In Tertiary Referral Hospitals. - Imtiaz, Marium; Anees, Muhammad; Gull , Shaista (Pakistan Journal of Kidney Diseases, 2021)
Objective: To determine socio-demographic features of hemodialysis patients. Materials and method: Two hundred End Stage Renal Disease (ESRD) patients undergoing maintenance hemodialysis (MHD) were enrolled in the study. Sociodemographic, clinical and laboratory data was collected. Results: Mean age was 48.11 ± 13.741 years. Males were 105 (52.5%) and females were 95(27.5%). Majority (53.5%) of the patients were in middle age group (44-64 years). Less than 10th grade of education was in 146 (73%) patients. One hundred and seventy-eight (89%) patients had income less than Rs. 30,000 per month. Most of the patients were diabetic (41.5%) and hypertensive (40%). Mean duration of dialysis was 20.41± 20.33 months and majority of the patients 123 (61.5%) were on dialysis for less than 10 months. Frequency of dialysis was twice weekly for 155 (77.5 %) of the patients and rest of the patients were on thrice weekly dialysis. Seventy-eight (39%) of the patients were hepatitis C+ve and 31 (15.5 %) were hepatitis B+ve. Out of 200 patients 137 (68.5 %) were anemic, 161 (80.5%) were hypoalbuminemic, 170 (85%) had transferrin saturation (TSAT) less than 20%. Majority (62.5 %) patients were hyponatremic. Conclusion: In this study we found that majority of the patients on dialysis in tertiary referral hospitals weremale, middle aged, belonged to low socio-economic class and were having twice weekly dialysis. Hypertension and diabetes remain the leading causes of renal failure and hence dialysis. Most of the patients were malnourished.